2013
DOI: 10.1097/hjh.0b013e32835a34bb
|View full text |Cite
|
Sign up to set email alerts
|

Target organ damage assessment in French hypertensive patients without established cardiovascular or renal disease

Abstract: Subclinical TOD modalities are commonly assessed in French hypertensive patients without established cardiovascular or renal diseases, although 55% still do not benefit from combined triple LVH, macrovascular and renal assessment. The new modalities of TOD assessment are rarely implemented. Moreover, TOD assessment displayed poor effectiveness in upgrading cardiovascular risk classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
(11 reference statements)
0
2
0
2
Order By: Relevance
“…However, in our subgroup analysis, black women have a similar response to surgery as black men, with significantly higher MAP compared to non‐black women. Many of the long‐term detrimental effects of PA are secondary to prolonged exposure of the vasculature and target organs to elevated aldosterone that may lead to vascular remodeling and irreversible changes . In our cohort, black patients presented both with a longer duration of hypertension and larger burden of comorbid disease.…”
Section: Discussionmentioning
confidence: 93%
“…However, in our subgroup analysis, black women have a similar response to surgery as black men, with significantly higher MAP compared to non‐black women. Many of the long‐term detrimental effects of PA are secondary to prolonged exposure of the vasculature and target organs to elevated aldosterone that may lead to vascular remodeling and irreversible changes . In our cohort, black patients presented both with a longer duration of hypertension and larger burden of comorbid disease.…”
Section: Discussionmentioning
confidence: 93%
“…Sin embargo, en la práctica, menos del 15% de los clínicos investigan el daño cerebral producido por la HA. [4] El cerebro es una diana temprana del daño por HA. [1,5] Las lesiones cerebrovasculares subclínicas o silentes se detectan frecuentemente en pacientes asintomáticos mediante la neuroimagenología.…”
Section: Introductionunclassified
“…Como la HA es tan frecuente, los clínicos buscan cuidadosamente signos de daño en los órganos. Actualmente existen numerosas evidencias acerca del papel crucial del daño subclínico en los órganos, [1,4,7] bien establecido para las enfermedades cardiovasculares y renales debido a que las técnicas aplicadas están ampliamente disponibles. En cambio, la detección del deterioro temprano del cerebro requiere de técnicas de imagenología muy escasas y costosas para ser usadas de forma rutinaria en la práctica médica general.…”
Section: Introductionunclassified
“…The most common target organ damage associated with hypertension is left ventricular hypertrophy (LVH) [1][2][3]. An epidemiologic study revealed that the incidence rate of LVH in hypertension in the Chinese population is up to 42.7% [4].…”
Section: Introductionmentioning
confidence: 99%